ELIMINATION OF POLLUTIONS IN THE ATMOSPHERIC AIR'RGANISH - Halmatov Misliddin Muhammato‘vich; Xodjakulov Muxtorjonc (Journals Park Publishing, 2022)
This article aims to reveal the problems of the spread of pollutants in the air on the example of the city of Andijan. This research method may be necessary in the future to reveal the laws of atmospheric distribution of pollutants in cities. To date, the development of models that take into account the factors affecting atmospheric pollution is based on the equations of mass migration of aerodynamics in expressing the distribution of pollution into the atmosphere, taking into account complex processes.
Keywords: urban air purification; sludge; soil moisture